2018
DOI: 10.1038/s41467-018-07072-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the π-π-π stacking mechanism and DNA-binding activity of the YEATS domain

Abstract: The YEATS domain has been identified as a reader of histone acylation and more recently emerged as a promising anti-cancer therapeutic target. Here, we detail the structural mechanisms for π-π-π stacking involving the YEATS domains of yeast Taf14 and human AF9 and acylated histone H3 peptides and explore DNA-binding activities of these domains. Taf14-YEATS selects for crotonyllysine, forming π stacking with both the crotonyl amide and the alkene moiety, whereas AF9-YEATS exhibits comparable affinities to satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 36 publications
4
54
0
Order By: Relevance
“…Though future work is warranted, these findings offer a new avenue to pinpoint the role of benzoyl-CoA metabolism in gene regulation and beyond. Moreover, our structural studies provide key insights into molecular engineering of preference-switched acylation readers, an intriguing strategy that has been adopted to explore the functional importance of histone modification and its readout ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though future work is warranted, these findings offer a new avenue to pinpoint the role of benzoyl-CoA metabolism in gene regulation and beyond. Moreover, our structural studies provide key insights into molecular engineering of preference-switched acylation readers, an intriguing strategy that has been adopted to explore the functional importance of histone modification and its readout ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…When OD reached to 0.6, H3 expression was induced at 37 °C by adding 0.5 mM IPTG, 0.2% (w/v) l -arabinose and 5 mM AcK into cell culture. Cells were harvested 6 h after induction, and purified in the same steps as previously reported 51 . The whole procedure of CrK ( N -ε-crotonyl- l -lysine) incorporation into the K14 position of histone H3 was identical with AcK incorporation, except that pEVOL-MmPylRS-384W vector was used, and 1 mM of CrK ( N -ε-crotonyl- l -lysine) was added into 2YT medium after induction.…”
Section: Methodsmentioning
confidence: 99%
“…The AF9 YEATS domain can bind to several K Cr marks on histone H3 (K9, K18, K27) as well as K Pr and K Bu marks [105], while Taf14 binds preferentially to H3K9 Cr [106] and YEATS2 to H3K27 Cr [107]. Using a mutated version of TAF14 designed to selectively bind H3K9 Cr over H3K9 Ac ; Klein et al [108] were able to show that there may be a differential requirement of H3K9 Ac and H3K9 Cr in the expression of TAF14-regulated genes. More recently it has been suggested that the YEATS domain of GAS41 is a pH-dependent reader of H3K122 Succ [109], hinting that there may be a further expansion of the reading capabilities of the YEATS domain family (reviewed in [110]).…”
Section: Physiological Roles Of Diverse Acylationsmentioning
confidence: 99%